Effects of Heated Tumescence Solution in Bitches after Unilateral Mastectomy - Rocha, Fabiana Del Lama [UNESP] (2022)
Background: Mammary tumors, for which mastectomy is the main treatment, are the most common neoplasms in bitches. Mastectomy is painful and, in order to reduce the pain stimulus in the transoperative period, tumescent local anesthesia is associated with general inhalation anesthesia. However, despite the numerous benefits of tumescence, intraoperative hypothermia is the most common complication. In Medicine, especially in plastic and dermatological surgery, it is common to use a heated tumescence solution to prevent intraoperative hypothermia; however, in Veterinary medicine, no previous study has examined the advantages and disadvantages of using heated tumescence solution. Thus, this study aimed to investigate the transanesthetic cardiorespiratory effects of heated tumescence solution in bitches submitted to radical unilateral mastectomy. Materials, Methods & Results: Eight animals were treated with 0.1% lidocaine solution, warmed to 37-42°C, using a Klein’s cannula for administration. Chlorpromazine (0.3 mg/kg) and meperidine (3 mg/kg) were used as pre-anesthetic medication intramuscularly, and induction was performed with intravenous propofol and maintenance with isoflurane. The data collection times were as follows: 15 min after starting isoflurane administration (M1), 5 min after tumescence (M2), after beginning of surgical incision (M3), during breast pullout (M4), after clamping of the superficial caudal epigastric vein, and artery (M5), after the beginning of the approximation of the subcutaneous tissue (M6), after the beginning of the intradermal suture (M7), and at the end of the surgical procedure (Mfinal). The heart (HR) and respiratory (ƒ) rates, mean arterial pressure (MAP), end-tidal CO2 concentration (EtCO2), expired isoflurane concentration (EtISO), and rectal temperature (RT) were measured. The HR, ƒ, and EtCO2 levels did not differ statistically. The mean EtISO presented in M2 (1.16 ± 0.41) was significantly lower than that in M3 (1.39 ± 0.40) and M4 (1.49 ± 0.49). Discussion: In the HR analysis, it was found that during all evaluation moments, the means remained within the reference range for the species. Moreover, the values during the breast pullout (M4) did not exceed 20% of those presented minutes before the beginning of the surgery (M2), which was indicative of analgesic rescue, suggesting that the animals did not experience pain. Hypoventilation resulted in an increase in EtCO2 values. Thus, it can be said that in this study, there was no respiratory depression during the transoperative period, as the values of the variables ƒ and EtCO2 were within the reference for the species. With regard to the EtISO variable, there was no reduction in the MAC of isoflurane with the use of heated tumescence solution, as reported by some authors (EtISO 0.8%). However, the EtISO values presented here are close to those found in the literature during breast pullout (EtISO between 1.3% and 1.52%), with the use of refrigerated tumescence solution. In addition, the values shown in M4 are within the equivalent of 1 MAC (1.41%) of isoflurane, proving that heated tumescent local anesthesia is a safe technique and an excellent adjunct to inhalation anesthesia, as it provides intraoperative analgesia. Therefore, heated tumescence solution is safe and an excellent adjuvant in general inhalational anesthesia for radical unilateral mastectomy as it did not increase inhaled anesthetic consumption during surgery.